ANALYSIS OF THE HYPHOTESIS OF INCOME CONVERGENCE FOR THE MUNICIPALITIES OF THE MICROREGION OF CORNÉLIO PROCÓPIO – PR BETWEEN 1991 AND 2010 - Geovani Aparecido de Oliveira David; Leandro Garcia Meyer (Economia & Região, 2018)
This paper studied the economic scenario and to investigate the hypothesis of per capita income convergence among the Municipalities of the Microregion of Cornélio Procópio, which is located on the north part of the State of Paraná, Brazil. In order to study the convergence hypotheses, the traditional tests of β-convergence absolute and of σ-convergence were calculated for the years between 1991-2010, and the results showed that the poorer Municipalities have obtained a higher growth of per capita income compared to higher income Municipalities, confirming the convergence hypothesis for this period. However, even though the economic growth had reduced the income differences, it was also verified that the convergence speed was low. Therefore, the disparities are still expressive, mainly when comparing minor Municipalities, such as Santa Amelia, Congonhinhas and New America of Colina, with Cornélio Procópio, regional pole which presented the greater income level and economic activity in this Microregion. It was also noted that even Cornélio Procópio has low income in relation to other municipalities in the north region of the State of Paraná, such as Londrina and Maringá. Finally, it is important to highlight that the study’s results contribute to guide public